Upper airways in aspirin-exacerbated respiratory disease. Issue 1 (February 2015) - Choi, Jeong-Hee; Kim, Ji-Hye; Park, Hae-Sim
<x xml:space="preserve">Abstract</x> Purpose of review This review updates the status of chronic rhinosinusitis with nasal polyps (CRSwNP) in aspirin-exacerbated respiratory disease (AERD) in the contexts of epidemiology, diagnosis, pathogenesis, and treatment. Recent findings Recent studies have shown that prostaglandin E2 (PGE2) deficiency induces an AERD phenotype in PGE2 synthase-1 knock-out mice and also PGE2 resistance in granulocytes of AERD patients. The numbers of platelet-adherent leukocytes increase in AERD patients, enhancing production of cysteinyl leukotrienes (CysLTs) via transcellular metabolism of arachidonate. INF-γ released from eosinophils of the sinus tissue of AERD patients promotes eosinophil maturation, increases leukotriene-associated gene expression, and releases CysLTs. The serum periostin level has been suggested to be a useful biomarker predicting the AERD/CRSwNP phenotype. Aspirin desensitization was reported to decrease the levels of CD4+ T cell-derived cytokines, including INF-γ and IL-10, in line with the newly defined role of INF-γ in AERD. Summary Recent findings further support the notion that arachidonic acid metabolism is dysregulated in AERD patients. This is reflected by resistance to PGE2, overproduction of CysLTs by enhanced numbers of platelet-adherent leukocytes, and cellular stimulation by INF-γ released from eosinophils. Aspirin desensitization may be a useful treatment option in AERD patients exhibiting recalcitrant CRSwNP.